Water Governance of Singapore in Achieving Sustainable Water Security - Theresia Octastefani; Bayu Mitra Adhyatma Kusuma (Indonesian Journal of Environment and Sustainable Development, 2016)
Nowadays, the supply of clean water in the world is declined because of the human population growth pressure. So that water security is a real challenge for the people in the twenty-first century. More than a third of the world's population is not fulfilled the need for clean water, both for drinking water and sanitation. Various policies through the water governance need to be done in addressing the water crisis. It is because state/government remains the locus of power in managing natural resources for development. Singapore is one of country which previously experienced major problems in the availability of fresh water. Since separation from Malaysia in 1965, water becomes a major problem. Singapore does not have a clean water source because geographically Singapore is surrounded by beaches. This research will focus on how is the water governance in Singapore can achieve sustainable water security. Furthermore, to elaborate data, this research uses qualitative method with descriptive analysis approach. The result of research shows that to overcome the water crisis problem, the governments of Singapore take steps that are very creative and innovative to manage water independently with the goal to achieve water self-sufficiency and water security. Through the Public Utilities Board (PUB) program, Singapore's government cans fulfill the water needs for the people. Singapore implemented water governance by designing a comprehensive water management strategy which consisting from the protection and expansion of its water sources, reclamation of wastewater, desalination, demand management, and public education and awareness programs. Holistic approach to water governance has allowed Singapore to achieve sustainable water self-sufficiency and water security which is one of the best examples for innovative water management in the world.Keywords: Security Concept, Water Governance, Water Security